Study of the effect of common infusions on glass ionomers using the PIXE and RBS techniques - Verón, María Gisela (2017)
The effect of four commonly consumed beverages as mineral water, coffee, tea and mate tea on the elemental composition of a commercial glass ionomer was studied using Particle Induced X-ray Emission (PIXE) and Rutherford backscattering (RBS) techniques. We found that after immersion in acidic media, some elements as Al, Si and Na are lost from the glass-ionomer whereas others heavier, as K, Ca and La, increase their concentration at the surface. Although the concentration profiles of Al and Si are different in different media, in all of them the Al:Si ratio was close to unity and remained constant for different periods of immersion in all media. The incorporation of K, Mg and Fe to the surface is found for common infusions while for mineral water the glass-ionomer mainly loses F and Na.The RBS technique showed that immersion in different media produced a modification of the density of the glass ionomer surface layer due to the increment of the concentration of heavier elements at the surface. The thickness of the modified surface layer extends up to 3 µm when the immersion time is seven days and more than 6 µm after 33 days of immersion.